Case report: Pulmonary amyloidosis in two patients with chronic obstructive lung disease (COPD) - Haya Mardahayev; Sara Mohammed; Khalid Moddathir Mohmmed; Hala Rizalla; James Hayes (Respiratory Medicine Case Reports, 2019)
We present two cases of patients with chronic obstructive lung disease (COPD) who developed different forms of pulmonary amyloidosis. In both cases malignancy was considered as primary diagnosis. Transthoracic biopsy confirmed pulmonary amyloidosis.In the first case the patient presented with progressive dyspnoea over a two years period. Initial assessment was consistent with a diagnosis of COPD but progressive changes in symptoms and lung functions and subsequently CT Thorax revealed possible airway obstruction. Bronchoscopy confirmed an obstructive lesion initially considered to be malignant but was found to be due to tracheobronchial amyloid (TBA).Our second case presented with symptoms and signs consistent with COPD. Follow up chest X-rays revealed a pulmonary nodule which on CT examination was considered to be malignant. Transthoracic biopsy confirmed pulmonary amyloidosis.Although it is a rare condition amyloid disease should to consider as the part of the differential diagnosis in COPD patients who present with signs and symptoms consistent with pulmonary malignancy. Keywords: Tracheobronchial, Amyloidosis, Chronic obstructive lung disease, Pulmonary malignancy, Bronchoscopy, Transthoracic biopsy